Oral History Interview: History in Panama (Kern County) Mary Ashe interviewed by Jose A. Benavides - Ashe, Mary; Benavides, Jose A.
: Mary Ashe was born in Kern County in 1893 and lived in an area called Panama within the town of Bakersfield. Her farming family came from Chapel Hill, North Carolina in 1868 motivated by rumors that Kern County had developed irrigation. Ash first recounts the history of Kern County from the 1860s onward and then goes on to describe early farming life in the area. She describes pioneer life in Kern County, and how families like hers existed by growing gardens, owning dairies, and keeping livestock. She recalls in detail many of the families and businesses that were in the area early on, and discusses the Panama school which she attended.